Computational fluid mechanics and massively parallel processors - Sethian, J. A. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
The author reports on work devising massively parallel implementations of vortex methods for computing turbulent flow in highly complex geometries. The challenges involved in fitting evolving compilers, hardware, and I/O to nontraditional fluid mechanics techniques, N-body solvers, and interactive real-time visualization environments are discussed. The results describe algorithms to compute two and three-dimensional inside chambers and around bluff bodies. Some issues involved in developing intuition about parallel implementation of complex codes are examined.